MEMBANGUN PROFIL RESIKO PADA PEMBUATAN PETA DIGITAL MENGGUNAKAN FRAMEWORK NIST - Koes Wiyatmoko; Yudi Prayudi (Cyber Security dan Forensik Digital, 2018)
GPS (Global Positioning System) is the main device that record location based on coordinate . The purpose of location recording is making digital maps and the output are printed-maps. Digital maps and printed-maps that have been authorized by the government will become reference for every activities like terminating the location objects or borderline. The Accuracy and authenticity of coordinate data from GPS is essential for high-accuracy maps, but digital maps are also vulnerable from editing, duplication, or deleted for a particular purpose. Because of that, supervisory management in the manufacturing process is needed to help facilitate in building a digital map-making profile. The reference in managing risk management to build the profile is NIST Framework.